Pengaruh Literasi Keuangan dan Financial Technology Terhadap Kinerja Keuangan UMKM - Lubis, Era Fazira MD; Nurhayati, Nurhayati (Forum Kerjasama Pendidikan Tinggi, 2024)
The purpose of this research is to see the effect of financial literacy and financial technology (fintech) on the financial performance of MSMEs in Tanah Enam Ratus Village, and to identify factors that influence the level of financial literacy and the use of financial technology (fintech) among MSMEs in Tanah Enam Ratus Village. This research was conducted on MSMEs in the culinary sector in Tanah Enam Ratus village. The type of data analysis method used in this research is a quantitative descriptive approach. The data analysis techniques used in this study include normality test, multicolinerity test, heteroscedasticity test, multiple linear regression test, and validity and reliability tests to test the questionnaire before being distributed to real respondents. Finally, hypothesis testing using the t test, simultaneous f test, and coefficient of determination (r2) test and this test is assisted by SPSS version 25. The results showed that partially financial literacy has a negative effect and significantly affects the financial performance of MSMEs in the Tanah Enam Ratus village, and partially financial technology (fintech) has a negative effect and significantly affects the financial performance of MSMEs in the Tanah Enam Ratus village. Finally, simultaneously financial literacy and financial technology (fintech) have a positive and significant effect on the financial performance of MSMEs in the Tanah Enam Ratus village.